Legal Protection Theory for Inclusiveness Focusing on the Fulfillment of the Right to Work - Dyah Hapsari Prananingrum; Thyrone Jehuda Mandagi (Journal of Law, Politic and Humanities, 2026)
Learning from local cases to be adopted in a global context, especially the right to work for people with disabilities and the role of foundations in Yogyakarta as intermediaries for disabled workers' partners with companies. This study focuses on how the law provides protection for the right of inclusion to work as a fulfillment of human rights and the role of foundations in this context. This research attempts to evaluate existing laws and policies related to inclusion and provide suggestions for legal development needed in the legal protection law frame. This research is a legal research using empirical legal methodology where reliable data is collected directly from field evaluation. The main techniques for collecting data are interviews with key informants and documentary research. This research utilizes qualitative analysis, which is conducted concurrently with the data collection procedure. This study concludes that to strengthen inclusiveness in inclusive labor standards, laws and internal regulations must be made to regulate.